Strategic Development of Aurantiochytrium sp. Mutants With Superior Oxidative Stress Tolerance and Glucose-6-Phosphate Dehydrogenase Activity for Enhanced DHA Production Through Plasma Mutagenesis Coupled With Chemical Screening - Nazir, Yusuf; Phabakaran, Pranesha; Halim, Hafiy; Mohamed, Hassan; Naz, Tahira; Abdul Hamid, Aidil; Song, Yuanda (Frontiers in Nutrition, 2022)
Thraustochytrids such as Aurantiochytrium and Schizochytrium has been shown as a promising sustainable alternative to fish oil due to its ability to accumulate a high level of docosahexaenoic acid (DHA) from its total fatty acids. However, the low DHA volumetric yield by most of the wild type (WT) strain of thraustochytrids which probably be caused by the low oxidative stress tolerance as well as a limited supply of key precursors for DHA biosynthesis has restricted its application for industrial application. Thus, to enhance the DHA production, we aim to generate Aurantiochytrium SW1 mutant with high tolerance toward oxidative stress and high glucose-6 phosphate dehydrogenase (G6PDH) activities through strategic plasma mutagenesis coupled with chemical screening. The WT strain (Aurantiochytrium sp SW1) was initially exposed to plasma radiation and was further challenged with zeocin and polydatin, generating a mutant (YHPM1) with a 30, 65 and 80 % higher overall biomass, lipid and DHA production in comparison to the parental strains, respectively. Further analysis showed that the superior growth, lipid and DHA biosynthesis of the YHMP1 were not only attributed to the higher G6PDH and enzymes involved in the oxidative defence such as superoxide dismutase (SOD) and catalase (CAT), but also to other key metabolic enzymes involved in lipid biosynthesis. This study provides an effective approach in developing the Aurantiochytrium sp mutant with superior DHA production capacity that has the potential for industrial applications.